Analysis Of The Effect Of Work-Life Balance, Self-Esteem And Work Motivation On Organizational Commitment Moderated By Organizational Justice On Workers In Yogyakarta - Syamsul Hadi; Efni Pebrianti; Kusuma Chandra Kirana (STKIP Singkawang, 2023)
The purpose of this study is to impact the effect of work-life balance, self-esteem and work motivation on organizational commitment moderated by organizational justice in the workforce at Yogyakarta. This research is quantitative. The population in this study was the entire workforce at Yogyakarta. The sample used in this study was 100 employees. The sampling technique in this research is non-probability sampling using purposive sampling. Data was collected by distributing questionnaires. The data analysis technique used is the inner model and path analysis. The data that has been obtained is processed using SmartPLS 3.0. the results of this study indicate that work-life balance has a positive and significant effect on organizational commitment; self-esteem has a positive and significant effect on organizational commitment; work motivation has a positive and significant effect on organizational commitment; work-life balance, self-esteem and work motivation have a positive and significant effect on organizational commitment moderated by organizational justice.